THE RELATIONSHIP BETWEEN KNOWLEDGE AND BEHAVIOR OF ADOLESCENTS REGARDING THE EFFECTS OF COFFEE ON TOOTH DISCOLORATION IN PONTIANAK PEOPLES COFFEE SHOP: PENGETAHUAN REMAJA TENTANG EFEK KOPI TERHADAP TERJADINYA STAIN - Marsinda, Melly; Haryani , Nike; Setiawaty Ningsih, Neny; Herlina, Rita; Rusmali, Rusmali (JURNAL TERAPIS GIGI DAN MULUT, 2025)
Teeth discoloration is a problem of dental aesthetic disorders. If the color of the teeth is yellow, brownish, blackish will make a person's loss of self-confidence. Stains are stainings that adhere to the surface of teeth as a result of consuming colored drinks and foods. Coffee contains tannin compounds that contain dyestuffs so that it easily affects teeth discoloration. Eating coffee is a favorite behavior in today's teenagers. The health status of the teeth and mouth is also influenced by behavior, if bad behavior the impact on dental health will also be bad, and vice versa. The behavior of a person can be formed from the factor of knowledge. Lack of knowledge can shape erroneous behaviors and attitudes. This study aims to determine adolescents' knowledge about the effect of coffee on changes in tooth color (stain) and the relationship between knowledge and behavior of consuming coffee in adolescents. The research method uses a descriptive quantitative method of analytical survey with a cross-sectional approach. The subjects of this study were 47 teenagers who were in a pontianak folk coffee shop. The results of the knowledge research of respondents before being given counseling were in the category of less than 35 people (74.5%), while the criteria for respondents' behavior were included in the bad category as many as 42 people (89.4%). The results of data analysis using the spearman test obtained a p value of 0.000 (<0.005) which showed that there was a correlation between knowledge and behavior in adolescents with a coefficient value of 0.633. The conclusion of this study is that adolescents are still lacking in understanding the causes that can cause discoloration in teeth (stains), one of which is coffee and there is a strong correlation between knowledge and behavior. Keyword : Knowledge, Behavior, Teeth discoloration.